MANAGEMENT OF ACROMEGALY WITH AYURVEDA- A CASE STUDY - Divya, *Kajaria; Gupta, Arun (International Journal of Ayurveda and Pharma Research, 2016)
Acromegaly is a disease caused by excessive secretion of growth hormone by pituitary gland due to tumour (adenoma). Excessive secretion of growth hormone causes disfigurement and if this affects internal organs it may cause even death. Management of Acromegaly by contemporary medicine is not very successful as surgery (in non- permissible conditions), radiation therapy and use of somatostatin analog, growth hormone antagonist etc., all have limited role and are not able to annihilate the disease. The paper gives the description of a known case of Acromegaly presented with all the cardinal sign and symptoms along with major complications (venous obstruction, loss of peripheral vision, etc.). The patient was taking contemporary medicines from the starting of appearance of sign of disease but didnt get any significant relief therefore he came to seek Ayurvedic treatment. The patient was managed with Ayurvvedic medicines and Panchakarma procedure including Shirodhara for duration of 15 days. Total two sitting of Shirodhara were given one month apart showed considerable improvement in all the presenting symptoms. The increasing sole size, diminished vision and excessive sweating were remarkably reduced with the improvement of overall well being of the patient.